2011
DOI: 10.1038/ejcn.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of industrial and ruminant trans fatty acids and risk of coronary heart disease: a systematic review and meta-analysis of cohort studies

Abstract: The aim of this systematic review and meta-analysis was to summarize the evidence from observational studies assessing the association between intake of trans fatty acids (TFA) and the risk of coronary heart disease (CHD), with a specific emphasis on distinguishing between TFA of industrial and ruminant origin. By searching five bibliographic databases, analyses from six published and two unpublished prospective cohort studies, assessing the association of intake of TFA with fatal and/or non-fatal CHD, were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(148 citation statements)
references
References 31 publications
11
133
1
3
Order By: Relevance
“…Replacing SFA with carbohydrate was not clearly protective. Bendsen et al (2011) Comparison of effect of industrial (PHVO) and dairy-derived TFA on CHD risk. On the basis of nine cohort studies.…”
Section: Diet-heart Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing SFA with carbohydrate was not clearly protective. Bendsen et al (2011) Comparison of effect of industrial (PHVO) and dairy-derived TFA on CHD risk. On the basis of nine cohort studies.…”
Section: Diet-heart Hypothesismentioning
confidence: 99%
“…Somewhat surprisingly, only minor changes were seen in plasma lipoproteins with both sources of TFA compared with baseline diet, and the authors concluded that no conclusions could be drawn 'about the effect of TFAs from either source on absolute CVD risk in these normolipidemic subjects' (Chardigny et al, 2008). In a recent metaanalysis, Bendsen et al (2011) compared the impact of industrial (PHVO) and ruminant TFA on risk of CHD. The review of nine prospective cohort studies concluded that, although high intakes of total TFA were associated with increased CHD events and mortality, there were no significant effects of either industrial or ruminant sources (although the impact of the former on CHD risk was close to significant, P 5 0.09).…”
Section: Tfa and Cardiovascular Riskmentioning
confidence: 99%
“…The consumption of dietary TFA has long been suspected of increasing the risk of CHD (105) and a number of epidemiological studies have reinforced this hypothesis (106)(107)(108) . The current UK population intakes of TFA are, on average, well below the maximum of 2 % of total energy intake set by the Department of Health (109) , at approximately 0·7 % of total energy (7) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…However, the isomer distribution of ruminant (normally mainly trans-vaccenic acid; trans-18 : 1n-7) and industrially (mainly elaidic acid; trans-18 : 1n-9) produced TFA are different and have been shown to have differential effects on the risk of CHD (110) . In addition, a recent meta-analysis of observational studies showed that industrially produced TFA may be positively associated with CHD (RR 1·21; 95 % CI 0·97, 1·50; P = 0·09), whereas ruminant TFA was not (RR 0·92; 95 % CI 0·76, 1·11; P = 0·36) (105) . Similar differential effects of ruminant and industrial TFA were reported in the recent meta-analysis of de Souza et al (111) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…Since it is solid at room temperature and its fractions deliver a wide range of functional melting profiles, palm oil has played an important role in the replacement of partially hydrogenated oils in food applications in Western Europe. Due to the fact that partially hydrogenated oils can contain a significant amount of trans ‐fatty acids, which are considered as unhealthy 1, their use and application has steadily decreased since the mid‐90's. In many countries (and the number is growing) there are legal limits for the level of trans ‐fatty acids in foods, which very often lead to the situation that partially hydrogenated fats have been replaced by palm oil or palm kernel oil based products, which both come from the oil palm tree ( Elaeis guineensis ).…”
Section: Introductionmentioning
confidence: 99%